2021
DOI: 10.1177/20499361211039379
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge assessment of anti-snake venom among healthcare practitioners in northern Nigeria

Abstract: Introduction: Anti-snake venom (ASV) is the standard therapy for the management of snakebite envenoming (SBE). Therefore, the knowledge of ASV among healthcare practitioners (HCPs) is essential for achieving optimal clinical outcomes in snakebite management. This study aimed to assess knowledge of ASV among the HCPs in northern Nigeria. Methods: We conducted a cross-sectional study involving eligible HCPs from different healthcare settings in northern Nigeria. The participants were recruited into the study usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Sixteen studies [2,4,14,16,18,19,28,[35][36][37][38][39][40][41][42][43] from 12 countries or territories, reporting knowledge of snakebite and snakebite management from 7,640 participants, were included in the quantitative analyses. All studies included in the analysis were online or hospital-based crosssectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies [2,4,14,16,18,19,28,[35][36][37][38][39][40][41][42][43] from 12 countries or territories, reporting knowledge of snakebite and snakebite management from 7,640 participants, were included in the quantitative analyses. All studies included in the analysis were online or hospital-based crosssectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the importance of basic knowledge and awareness concerning snakebite envenoming, multiple studies have found that many healthcare workers in snakebite endemic regions have poor general knowledge of the snakebite crisis [ 14 ]. A study by Michael and colleagues reported that doctors in Nigeria had poor knowledge of venomous snakes, snakebite first aid, treatment, and prevention [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Snakebite envenoming (SBE) is a neglected public health problem, especially in Asia, Latin America and Africa ( WHO, 2017 ) and is on the rise in Nigeria and other West African countries mainly due to paucity of anti-snake venom, poor treatment knowledge, and inadequate treatment centres ( Michael et al, 2018 ; Bala et al, 2021 ; Gutiérrez et al, 2021 ). The SBE affects poor communities in Asia and Africa, leading to compounded disadvantages with negative impacts on the economy and the healthcare sectors of the countries in the regions ( Habib and Brown, 2018 ).…”
Section: Introductionmentioning
confidence: 99%